2009
DOI: 10.1016/j.biomaterials.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-based fibrous scaffold for spatial organization of encapsulated and seeded human mesenchymal stem cells

Abstract: Living tissues consist of groups of cells organized in a controlled manner to perform a specific function. Spatial distribution of cells within a three-dimensional matrix is critical for the success of any tissue-engineering construct. Fibers endowed with cell-encapsulation capability would facilitate the achievement of this objective. Here we report the synthesis of a cell-encapsulated fibrous scaffold by interfacial polyelectrolyte complexation (IPC) of methylated collagen and a synthetic terpolymer. The col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
1
54
0
1
Order By: Relevance
“…However, current biomaterials used for scaffolding do not present a hierarchical structure as that found in natural materials and this could affect the cell behavior and differentiation. A rigorous understanding of collagen's scale and strain dependent stiffness may help in designing biomaterials with appropriate mechanical characteristics and thus addresses an immediate need for optimized matrix elasticity to foster differentiation and regeneration for regenerative medicine applications based on stem cell therapies such as cardiomyoplasty, muscular dystrophy, and neuroplasty [61][62][63]. To highlight the variation of Young's modulus and bending rigidity for a variety of biological and synthetic fibers we present a comparative analysis as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, current biomaterials used for scaffolding do not present a hierarchical structure as that found in natural materials and this could affect the cell behavior and differentiation. A rigorous understanding of collagen's scale and strain dependent stiffness may help in designing biomaterials with appropriate mechanical characteristics and thus addresses an immediate need for optimized matrix elasticity to foster differentiation and regeneration for regenerative medicine applications based on stem cell therapies such as cardiomyoplasty, muscular dystrophy, and neuroplasty [61][62][63]. To highlight the variation of Young's modulus and bending rigidity for a variety of biological and synthetic fibers we present a comparative analysis as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, poor mechanical properties necessitated post-fabrication treatment in the form of a sol-gel procedure. PEC fibers derived from methylated collagen and deprotonated terpolymer (2:1:1) of methyl methacrylate (MMA), 2-hydroxyethyl methacrylate (HEMA) and methacrylic acid (MAA) were prepared by Yow et al [7] to address the shortfalls of the earlier scaffolds. Integrin-rich collagen enhanced cellular interactions while terpolymer components afforded requisite physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously synthesized polyelectrolyte complexation (PEC) fibers from methylated collagen and synthetic terpolymer polyelectrolytes via interfacial polyelectrolyte complexation (IPC) for hMSC culture [7]. The ambient fiber drawing conditions avoid the denaturing of collagen and permit the formation of a bioactive PEC fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matthews et al demonstrated that collagen may be used to produce a nearly ideal scaffold for tissue engineering [59], whereas Yow et al showed that collagen can also be electrospun with other types of polymers, allowing efficient proliferation of human MSCs and maintenance of their multipotency for up to 7 days [60].…”
Section: Natural Polymersmentioning
confidence: 99%